Clinical Evaluation of Autologous Small Blood Stem Cells in Guided Bone Regeneration for Dental Implant Placement: A Phase I Study - Urooj, Mehwish; Siddiqui, Asma; Ahmed, Affan; Uddin, Muhammad Khawaja Hammad; Akram, Ayesha; Sabhi, Qudsia (Pakistan journal of medicine and dentistry, 2025)
Background: Autologous small blood (SB) stem cells, a new stem cell subtype present in the peripheral blood of adults, were found to exhibit regenerative capacities in bone regeneration. This phase I clinical study aimed to study SB cells' safety, tolerability, and early efficacy in guided bone regeneration (GBR) surgical procedures in cases of severe alveolar bone defects among patients who are to receive a dental implant. Methods: In a single-centre, dose-escalation, prospective 24-week study, fifteen patients who needed alveolar augmentation were recruited according to strict inclusion criteria and randomly assigned into three cohorts (n=5 each) to be treated with escalating doses of CD61−Lin− SB cells (1×10⁵, 1×10⁶, and 1×10⁷ cells). GBR was carried out with the help of a collagen membrane and bone graft substitute, followed by the transplantation of SB cells. Bone mineral density (BMD) was measured in Hounsfield Units (HU) by CT scan at baseline and weeks 2, 4, 6, 8, and 12 after treatment. Blood chemistries, immunologic markers, and safety profiles were measured as well. Results: No serious adverse events or dose-limiting toxicities were seen. HU scores significantly changed from baseline (mean: 485 HU) to week 12 (mean: 820 HU), reflecting enhanced BMD. Anaemia and leukocytosis resolved in patients, and liver toxicity was not observed. Immunoassays detected high cytokines (e.g., IL-17a, MCP-1), indicative of an ongoing tissue regeneration. Conclusions: SB cell-based GBR was tolerated and safe among patients with defects of the alveolar bone. Preliminary evidence indicates improved bone regeneration. Future phase II studies with larger sises are justified to confirm efficacy and hasten osseointegration.